The Impact of Leadership Style on Human Resources Performance in Organization Mediated by Organizational Silence - Reza Jafariharandy; Habibeh Najafi (مطالعات مدیریت بهبود و تحول, 2017)
Due to global competition, performance evaluation is required for the survival of the organization; main reason to assess and measure organizational performance is to increase the organization’s overall effectiveness and business processes. the aim of this study is to investigate the impact of leadership style on human resources performance in organization mediated by organizational silence. Research method is correlation based on structural equation modeling, the statistical population consist of Sari Sepah Bank branches official staff to number 430. The sample size was estimated by Cochran formula to number 203 that were selected by multistage random cluster sampling. The used instrument in this study is three standard questionnaires- leadership measurement Avolio (1997), organizational performance Echio (2003) and organizational silence Vandyne ;et al (2003) - On which their reliability were confirmed by factor analysis and have appropriate validity. Data were analyzed by SPSS software and LISREL. The results showed that transformational leadership style and exchange have positive and significant relationship with organizational performance. organizational silence have negative relationship with organizational performance. Transformational leadership enhances performance mediate by organizational silence and transactional leadership reduces performance mediate by organizational silence. Tansformational leadership have negative relationship with organizational silence. transactional leadership have positive relationship with organizational silence. Due to greater impact of transformational leadership in enhancing organizational performance in compared to transactional leadership and broke the silence; were recommended to banks managers to operate this leadership style in their plans as common style and dominant and enhance the performance of their organizations in today's competitive world .